Reaching 30% energy coupling efficiency for a high-density-carbon capsule in a gold rugby hohlraum on NIF. (23rd July 2021) - Ping, Y.; Amendt, P.; Baker, K.; Smalyuk, V.A.; Chen, H.; Khan, S.; Hartouni, E.P.; Ho, D.; Jones, O.; Landen, O.N.; Lemos, N.; Lindl, J.; et al.
Abstract: In the laser-driven indirect drive scheme for inertial confinement fusion, the energy coupling efficiency from the hohlraum to the capsule is typically ∼10% due to limited capsule sizes in order to attain quasi-round implosions with currently available laser energy in cylindrical hohlraums. Recent experiments at the National ignition Facility (NIF) showed ∼30% energy coupling efficiency to aluminum capsules by using a rugby-shaped hohlraum to accommodate larger capsules. This paper reports the first experiment at the NIF demonstrating ∼30% energy coupling to a 3 mm-diameter high-energy-density carbon capsule in a rugby hohlraum with a two-shock laser pulse shape. By comparing the measured bang time with a simulated hydrodynamic scaling, ∼430 kJ coupling is inferred with 1.36 MJ laser drive. The symmetry of the hot spot was observed to be more oblate than simulations predicted. X-ray images taken at late time show strong emission at the laser entrance hole of the rugby hohlraum, indicating a closure earlier than expected, which could contribute to the oblate hot spot shape. Implementing wavelength detuning or modifying the hohlraum shape to tune the symmetry in future experiments would allow symmetric implosions while maintaining the high energy coupling.